Beyond Compensation : Konstruksi Makna Kompensasi, Motivasi, dan Kepuasan Kerja dalam Konteks Budaya - Asania Waruwu; Ray Octafian (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to explore the meanings of compensation, motivation, and job satisfaction for garment industry workers within the context of Indonesian culture, responding to the phenomenon of high job dissatisfaction despite compensation meeting the regional minimum wage standards. Using an interpretivist phenomenological approach, the research was conducted at PT Sam-Sam Jaya Garments, located in the Bawen Industrial Area, Semarang Regency, over a period of eight months. Data were collected through semi-structured in-depth interviews with 18 informants (13 women and 5 men) from various job levels, participatory observations, and organizational document analysis. Thematic analysis using the interactive model of Miles and Huberman identified three main themes: compensation as a symbol of recognition and justice, encompassing material, symbolic, and relational dimensions; layered motivation consisting of survival, actualization, and contribution; and holistic job satisfaction that integrates material, relational, developmental, contributive, and spiritual dimensions. The findings reveal a unique concept of “collective compensation” in Javanese culture, where satisfaction is not solely determined by individual achievement but also by group success. The study develops an “Integrated Cultural Work Experience” model, showing that the three constructs operate within a dynamic system that mutually reinforces each other within the framework of local cultural values. The theoretical contributions include the development of a culturally responsive concept of compensation, motivation that integrates spiritual dimensions, and job satisfaction as a holistic phenomenon. Practical implications include the need for compensation systems that emphasize transparency and collective recognition, as well as motivational programs that integrate local cultural values. This research opens opportunities for developing more culturally sensitive and contextual human resource management theories.